2010
DOI: 10.1016/j.bbrc.2010.07.035
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic and duodenal homeobox 1 (PDX1) phosphorylation at serine-269 is HIPK2-dependent and affects PDX1 subnuclear localization

Abstract: Research highlights► Mouse PDX1 Ser-269 is phosphorylated in pancreatic islets of Langerhans and beta cells. ► High glucose concentration decreases the degree of phosphorylation on PDX1 Ser-269, as assessed by a phospho-specific anti-phospho-Ser269 antibody. ► HIPK2 is a potential kinase for PDX1 Ser-269. ► Phosphorylation at Ser-269 affects the subnuclear distribution of PDX1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 25 publications
0
25
0
Order By: Relevance
“…HIPK2 positively influences PDX1 levels and transcriptional activity, and directly phosphorylates the C-terminal portion of PDX1 [28]. HIPK2 is a potential kinase for PDX1 Ser-269, with high glucose concentrations decreasing the degree of phosphorylation on PDX1 Ser-269 in beta cells [42]. We showed that the number of PDX1-positive cells was reduced by 20% in Hipk3-knockout mice on a 12 week high-fat diet (Fig.…”
Section: Discussionmentioning
confidence: 78%
“…HIPK2 positively influences PDX1 levels and transcriptional activity, and directly phosphorylates the C-terminal portion of PDX1 [28]. HIPK2 is a potential kinase for PDX1 Ser-269, with high glucose concentrations decreasing the degree of phosphorylation on PDX1 Ser-269 in beta cells [42]. We showed that the number of PDX1-positive cells was reduced by 20% in Hipk3-knockout mice on a 12 week high-fat diet (Fig.…”
Section: Discussionmentioning
confidence: 78%
“…Recently it was shown that HIPK2 is expressed in the developing pancreatic epithelium from E12 to E15 and that its expression is confined preferentially to pancreatic endocrine cells later in development (171). Phosphorylation of the transcription factor, PDX-1, in the C-terminus by HIPK2, possibly at Ser-214 (172), was reported to increase the stability and transcriptional activity of PDX-1 (171). Our own data indicate that HIPK2 posphorylates PDX-1 at Ser-269 in the C-terminal portion of PDX-1 in pancreatic cells in vivo and that phosphorylation at this site leads to nuclear exclusion of PDX-1 and a decrease in PDX-1 target gene expression (172).…”
Section: Homeodomain Interacting Protein Kinase 2 (Hipk2)mentioning
confidence: 99%
“…Phosphorylation of the transcription factor, PDX-1, in the C-terminus by HIPK2, possibly at Ser-214 (172), was reported to increase the stability and transcriptional activity of PDX-1 (171). Our own data indicate that HIPK2 posphorylates PDX-1 at Ser-269 in the C-terminal portion of PDX-1 in pancreatic cells in vivo and that phosphorylation at this site leads to nuclear exclusion of PDX-1 and a decrease in PDX-1 target gene expression (172). As PDX-1 has been shown to directly bind to and regulate the promoter activity of various cell genes, e.g.…”
Section: Homeodomain Interacting Protein Kinase 2 (Hipk2)mentioning
confidence: 99%
“…At least three different post-translational modifications, including phosphorylation, sumoylation and glycosylation, have been suggested to explain nuclear-cytoplasmic shuttling and/or other functions of PDX1 [40][41][42][43][44][45][46]. Phosphorylation is a common post-translational modification implicated in the regulation of numerous transcription factors, but the precise role of PDX1 phosphorylation in the regulation of its subcellular localisation and activity remains unknown [40,41,47].…”
Section: Mst1-pdx1: a Deleterious Interaction Compromising Beta Cell mentioning
confidence: 99%